f(x) = 2x^3 – 7x^2 + 4x + 4 (a) Use the factor theorem to show that (x – 2) is a factor of f(x). (2) (b) Factorise f(x) completely.

We are presented with a third order polynomial with 4 terms, so we expect 3 solutions for f(x)=0. To prove that (x-2) is a factor we must insert the value of x=2 into the function and if f(2)=0 then we have verified that (x-2) is a factor. We can now perform long division using the property of polynomials (which states that a polynomial is divisible by it's factors) to simplify f(x) by dividing through by (x-2).

This results in (2x^2 - 3x - 2), which can be simplied further via factorisation to produce (x-2)(2x+1). We have now fully factorised f(x) and can see that we have a repeated root at x=2 so even though f(x)=(x-2)(x-2)(2x+1) is a correct answer it is better practice to write the final answer as f(x)=(x-2)^2 (2x+1) so that the repeated root can be seen clearly.

To double check that (2x+1) is a factor we can insert the value of x=-1/2 such that f(-1/2)=0.

Answered by Nazar A. Maths tutor

13254 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve (3x+6)/4 - (2x-6)/5 = (x+7)/8.


How to prove that (from i=0 to n)Σi^2= (n/6)(n+1)(2n+1), by induction.


With log base 4, solve log(2x+3) + log(2x+15) = 1 + log(14x+5)


Expand and simplify (n + 2)^3 − n^3.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences